Penerapan Pembelajaran Matematika Materi Geometri di SDN 64/I Muara Bulian - Puput Tri Rosdianah; Violita Zahyuni; Ilhan Manzis (FONDATIA, 2022)
The problem in this study is how the process of learning mathematics on geometry material can be easily understood, enjoy, and does not make students feel bored with the material so that it can lead students to academic achievement at national and international levels. The purpose of this study is to describe the planning, implementation, evaluation, and obstacles in learning mathematics with geometry material. The research method uses descriptive qualitative. Data collection techniques are semi-structured interviews, non-participating observations, and documentation studies. The subjects of the study were lecturers of geometry experts, school principals, sixth grade mathematics teachers, and sixth grade students. The results showed that the planning, implementation, and evaluation of mathematics learning for class VI gemoteri materials went well, coherently, pleasantly and there no significant obstacles for teachers or students.